Polyethylenimine architecture-dependent metabolic imprints and perturbation of cellular redox homeostasis - Hall, Arnaldur; Parhamifar, Ladan; Lange, Marina Krarup; Meyle, Kathrine Damm; Sanderhoff, May; Andersen, Helene; Roursgaard, Martin; Larsen, Anna Karina; Jensen, Per Bo; Christensen, Claus; Bártek, Jiří; Moghimi, Seyed Moein (Biochimica et biophysica acta, 2015)
Polyethylenimines (PEIs) are among the most efficient polycationic non-viral transfectants. PEI architecture and size not only modulate transfection efficiency, but also cytotoxicity. However, the underlying mechanisms of PEI-induced multifaceted cell damage and death are largely unknown. Here, we demonstrate that the central mechanisms of PEI architecture- and size-dependent perturbations of integrated cellular metabolomics involve destabilization of plasma membrane and mitochondrial membranes with consequences on mitochondrial oxidative phosphorylation (OXPHOS), glycolytic flux and redox homeostasis that ultimately modulate cell death. In comparison to linear PEI, the branched architectures induced greater plasma membrane destabilization and were more detrimental to glycolytic activity and OXPHOS capacity as well as being a more potent inhibitor of the cytochrome c oxidase. Accordingly, the branched architectures caused a greater lactate dehydrogenase (LDH) and ATP depletion, activated AMP kinase (AMPK) and disturbed redox homeostasis through diminished availability of nicotinamide adenine dinucleotide phosphate (NADPH), reduced antioxidant capacity of glutathione (GSH) and increased burden of reactive oxygen species (ROS). The differences in metabolic and redox imprints were further reflected in the transfection performance of the polycations, but co-treatment with the GSH precursor N-acetyl-cysteine (NAC) counteracted redox dysregulation and increased the number of viable transfected cells. Integrated biomembrane integrity and metabolomic analysis provides a rapid approach for mechanistic understanding of multifactorial polycation-mediated cytotoxicity, and could form the basis for combinatorial throughput platforms for improved design and selection of safer polymeric vectors.
Keywords: homeostáza; polyethylenimin; vztah mezi dávkou a účinkem léčiva; Antioxidants; Kinetics; buněčné linie; glutathion; oxidační stres; Glutathione; buněčné dýchání; Oxidative Stress; transfekce; Molecular Structure; energetický metabolismus; Polyethyleneimine; Oxygen Consumption; Structure-Activity Relationship; lidé; Transfection; Homeostasis; Energy Metabolism; Reactive Oxygen Species; adenosintrifosfát; mitochondriální membrány; Cell Line; molekulární struktura; oxidace-redukce; Dose-Response Relationship, Drug; molekulová hmotnost; Adenosine Triphosphate; Oxidation-Reduction; antioxidancia; Cell Respiration; reaktivní formy kyslíku; Mitochondrial Membranes; vztahy mezi strukturou a aktivitou; Cell Survival; Molecular Weight; viabilita buněk; buněčná membrána; kinetika; spotřeba kyslíku; Cell Membrane; Humans